speB gene as a specific genetic marker for early detection of rheumatic heart disease in human - Kaushal, A.; Kumar, D.; Khare, S.; Kumar, A. (Cellular and Molecular Biology, 2012)
Streptococcus pyrogenic exotoxin B gene (speB) is chromosomally encoded pyrogenic and cardiotoxic virulence factor of S. pyogenes. Exotoxin B is produced only in a secreted form, as a 40 KD proprotein, which is subsequently processed to 28 KD in the mature form. Streptococcus pyogenes infection in human, causes initially pharyngitis due to inhalation of aerosols emitted by infected persons, develops rheumatic fever which leads to the rheumatic heart disease (damage of heart valves). The available detection methods are bacterial culture, Î²-hemolysis, bacitracin sensitivity, hippurate test, phadebact test, CRP (C-reactive protein), ESR and PCR. All these methods are either expensive or non-confirmatory and have some limitations. Available PCR methods take more time and require other test to confirm the disease. Our PCR based detection of Streptococcus pyogenes in human using specific primers of speB gene completes overall analysis in 80 min which is the minimum time reported so far for the confirmation of the disease. Amplicon of 423bp of speB gene can be used as a specific genetic marker as it does not show homology with other organisms for early detection of rheumatic heart disease. Our method is specific virulence gene based which is quick, economical and more sensitive as compared with other methods.